Ultra-light elastic composite foam material, preparation method thereof and sole

By using ultra-light elastic composite foaming materials in sports soles, the existing sole materials collapse and have poor resilience after long-term wear, achieving higher resilience and wear resistance, and improving wear comfort and service life.

CN115926440BActive Publication Date: 2025-04-01QUANZHOU PEAK SHOES

Patent Information

Application Number
CN202211329388.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-04-01
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

Existing sports shoes sole materials are prone to collapse and poor rebound after wearing for a long time, which affects the comfort and service life of the wear.

Method used

An ultra-light elastic composite foaming material is used, which consists of polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane and ethylene vinyl acetate copolymer. Through specific proportions and process treatment, the material's elasticity and wear resistance are improved.

Benefits of technology

This material has excellent performance in compression deformation, improved resilience, and wear resistance far exceeds that of ordinary EVA foamed materials, which can provide a lasting comfort experience and extend the service life of the sole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926440B_ABST
    Figure CN115926440B_ABST
Patent Text Reader

Abstract

The present application relates to the field of shoe material manufacturing technology, and in particular to an ultra-light elastic composite foam material, a preparation method thereof and a sole. The composite foam material comprises a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent and a coupling agent. The present application adds a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer and polyborosiloxane to ethylene vinyl acetate copolymer, and under the synergistic effect of the proportion of various components, the compression deformation and weight of the composite foam material are greatly reduced, so that the resilience of the composite foam material is greatly improved, the composite foam material is soft and comfortable, has excellent buffering and resilience performance, and excellent wear resistance (far exceeding ordinary EVA foam material), so as to meet the performance requirements of sports shoe soles and bring consumers a lasting comfortable experience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of shoe material manufacturing, and in particular to an ultra-light elastic composite foam material, a preparation method thereof, and a shoe sole. Background Art

[0002] With the rapid development of the sports shoe market, consumers have higher and higher requirements for the quality of sports shoe soles, which not only require fashionable appearance but also comfortable wearing. Therefore, the performance requirements for sole materials are also getting higher and higher. Among them, softness, comfort and lightweight are the main development trends.

[0003] Most of the existing sports shoe soles are made of wear-resistant ethylene vinyl acetate copolymer (EVA) foam material, but the soles made of EVA are hard and dense, and have poor cushioning and resilience. After wearing for a period of time, they will collapse and have poor resilience, which seriously affects the feeling of athletes wearing sports shoes. Summary of the invention

[0004] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained through the structures specifically pointed out in the description and the drawings of the description.

[0005] The purpose of this application is to overcome the above shortcomings and provide an ultra-light elastic composite foam material, a preparation method thereof and a sole. The ultra-light elastic composite foam material is soft and comfortable, has excellent cushioning and resilience, excellent wear resistance (far superior to ordinary EVA foam materials), and good recovery performance, thereby meeting the performance requirements of sports shoe soles and providing consumers with a lasting comfortable experience.

[0006] In a first aspect, the present application provides an ultra-light elastic composite foam material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent;

[0007] Based on the total mass of the composite foam material,

[0008] The mass content of the polyolefin elastomer is 10%-15%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 35%-45%, the mass content of the polyborosiloxane is 5%-10%, the mass content of the ethylene vinyl acetate copolymer is 20%-45%, the mass content of the foaming agent is 1.0%-3.5%, the mass content of the active agent is 2.4%-4.0%, the mass content of the bridging agent is 0.4%-0.7%, and the mass content of the coupling agent is 1.2%-1.8%.

[0009] The present application adds polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer and polyborosiloxane to ethylene-vinyl acetate copolymer. Under the synergistic effect of the proportions of various components, the compression deformation and weight of the composite foam material are greatly reduced, so that the resilience of the composite foam material is greatly improved. The composite foam material is soft and comfortable, has excellent cushioning and resilience properties, and is excellent in wear resistance (far exceeding ordinary EVA foam materials), thereby meeting the performance requirements of sports shoe soles and providing consumers with a lasting comfortable experience.

[0010] In some embodiments, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, ethylene vinyl acetate copolymer;

[0011] Based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer,

[0012] The mass content of the polyamide elastomer is 35%-45%, the mass content of the thermoplastic polyurethane elastomer is 5%-10%, the mass content of the EPDM rubber is 5%-10%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 10%-15%, and the mass content of the ethylene vinyl acetate copolymer is 20%-45%.

[0013] The present application modifies the molecular chains in the polyamide elastomer by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point and can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0014] In some embodiments, the polyborosiloxane is formed by reacting polydimethylsiloxane with boric acid at 250° C.-300° C. In polyborosiloxane, electron-deficient boron atoms obtain electrons from oxygen atoms with electron pairs in adjacent molecules, thereby forming BO cross-linking bonds. The BO cross-linking bonds absorb heat energy to activate and break at room temperature, so when subjected to force, the composite foam material has deformation properties like plasticine. When encountering high-speed impact, because the action time is shorter than the thermal break time of the cross-linking bonds, the molecules can form a network structure, showing characteristics such as shock absorption and high resilience.

[0015] In some embodiments, the mass ratio of the polydimethylsiloxane to the boric acid is 25:2-4. The present application can ensure that the electron-deficient boron atoms obtain sufficient electrons from the oxygen atoms with electron pairs in the adjacent molecules by reasonably controlling the mass ratio of the polydimethylsiloxane to the boric acid, thereby forming enough BO cross-linking bonds, so that the composite foam material can have the characteristics of compression deformation when subjected to force, and can form a sufficient network structure between the molecules when subjected to high-speed impact to show characteristics such as shock absorption and high resilience.

[0016] In some embodiments, the reaction time is 70h-74h. The present application can ensure that the electron-deficient boron atoms obtain sufficient electrons from the oxygen atoms with electron pairs in the adjacent molecules by reasonably controlling the reaction time of polydimethylsiloxane and boric acid, thereby forming enough BO cross-linking bonds, so that polyborosiloxane can play a greater role.

[0017] In a second aspect, the present application provides a method for preparing an ultra-light elastic composite foam material, the preparation method comprising the following steps:

[0018] Mixing once, placing the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent at 120° C.-150° C. for 7 min-10 min to form a first mixed material;

[0019] Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130°C-140°C for 2min-3min to form a second mixed material;

[0020] Granulation: placing the second mixed material at 80° C.-90° C. for granulation to form a composite material;

[0021] Foaming: placing the composite material at 160° C.-170° C. for foaming to form an ultra-light elastic composite foam material.

[0022] The present invention firstly blends polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene vinyl acetate copolymer, active agent, and bridging agent and performs a first banburying, then continues to add foaming agent and coupling agent for blending and a second banburying, then performs granulation and foaming, and finally obtains an ultra-light elastic composite foam material. The composite foam material is soft and comfortable, has excellent cushioning and rebound performance, excellent wear resistance (far superior to ordinary EVA foam material), and good recovery performance, thereby meeting the performance requirements of sports shoe soles and can bring consumers a lasting comfortable experience.

[0023] In some embodiments, the preparation method further comprises a step of preparing a thermoplastic elastic nylon composite ultra-light elastomer, and the preparation step is:

[0024] Adding polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer into a twin-screw extruder, blending and extruding, to obtain a thermoplastic elastic nylon composite ultra-light elastomer;

[0025] The blending time is 3 min-5 min, and the blending temperature is 200°C-230°C.

[0026] The present application modifies the molecular chains in the polyamide elastomer by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point and can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0027] On the third aspect, the present application provides a sole, which is made of an ultra-light elastic composite foam material that is foamed through a foaming mold and then heated, shaped, and cooled through a molding mold.

[0028] The present application utilizes ultra-light elastic composite foaming material to form an ultra-light elastic sole through foaming, heating, shaping and cooling, thereby reducing the weight of a single sole by about 60%. At the same time, the density of a single sole is only about 40% of the density of a traditional sole. In addition, the sole is soft and comfortable, has excellent cushioning and rebound properties, is excellent in wear resistance (far exceeding ordinary EVA foam soles), and has good recovery performance, which effectively solves the technical problem of the sole "becoming hard from soft and undergoing large permanent deformation" after long-term wear, greatly prolongs the service life of the sole, enhances the durability of the sole, and improves the wearer's wearing experience.

[0029] In some embodiments, the foaming temperature is 160° C.-180° C., and the foaming time is 400s-600s. The present application significantly improves the foaming ratio by reasonably controlling the foaming temperature and foaming time of the ultra-light elastic composite foaming material in the foaming mold.

[0030] In some embodiments, the heating temperature is 165°C-185°C, the heating time is 500s-700s, and the shaping pressure is 80kg / m 2 -100 kg / m 2 The present application improves the structural stability of the sole by reasonably controlling parameters such as heating and shaping.

[0031] By adopting the above technical solution, the beneficial effects of this application are:

[0032] The present application modifies the molecular chains in the polyamide elastomer by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point and can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0033] The present application adds polyamide elastomer, thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into a twin-screw extruder for blending, and modifies the molecular chains in the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point, can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0034] The present application adds thermoplastic elastic nylon composite ultra-light elastomer to make the resilience of the sole reach more than 60%, far exceeding the test standard of 55% in the conventional high-elastic industry, and effectively reduces the impact force of the ground.

[0035] The present application utilizes ultra-light elastic composite foaming material to form an ultra-light elastic sole through foaming, heating, shaping and cooling, thereby reducing the weight of a single sole by about 60%. At the same time, the density of a single sole is only about 40% of the density of a traditional sole. In addition, the sole is soft and comfortable, has excellent cushioning and rebound properties, is excellent in wear resistance (far exceeding ordinary EVA foam soles), and has good recovery performance, which effectively solves the technical problem of the sole "becoming hard from soft and undergoing large permanent deformation" after long-term wear, greatly prolongs the service life of the sole, enhances the durability of the sole, and improves the wearer's wearing experience.

[0036] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure.

[0037] Undoubtedly, these and other objects of the present application will become more apparent after the following detailed description of the preferred embodiment described with reference to various figures and drawings.

[0038] In order to make the above and other purposes, features and advantages of the present application more obvious and understandable, one or several preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings are used to provide further understanding of the present application and constitute a part of the specification. They are used together with the implementation methods of the present application to explain the present application and do not constitute a limitation to the present application.

[0040] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only one or several implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on such drawings without paying creative work.

[0041] Figure 1 This is a flow chart for preparing the ultra-light elastic composite foam material according to some embodiments of the present application;

[0042] Figure 2 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 1 of the present application;

[0043] Figure 3 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 2 of the present application;

[0044] Figure 4 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 3 of the present application. DETAILED DESCRIPTION

[0045] The following will describe the implementation methods of the present application in detail in conjunction with the accompanying drawings and embodiments, so that the implementation process of how the present application applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. It should be noted that as long as there is no conflict, the various embodiments in the present application and the various features in the embodiments can be combined with each other, and the technical solutions formed are all within the protection scope of the present application.

[0046] Meanwhile, in the following description, many specific details are set forth for the purpose of explanation to provide a thorough understanding of the embodiments of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without the specific details or the specific manner described herein.

[0047] In a first aspect, the present application provides an ultra-light elastic composite foam material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent;

[0048] Based on the total mass of the composite foam material,

[0049] The mass content of the polyolefin elastomer is 10%-15%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 35%-45%, the mass content of the polyborosiloxane is 5%-10%, the mass content of the ethylene vinyl acetate copolymer is 20%-45%, the mass content of the foaming agent is 1.0%-3.5%, the mass content of the active agent is 2.4%-4.0%, the mass content of the bridging agent is 0.4%-0.7%, and the mass content of the coupling agent is 1.2%-1.8%.

[0050] Polyolefin elastomer generally refers to polyolefin thermoplastic elastomer, which is a high-performance polyolefin that is rubber-elastic at room temperature and has the characteristics of low density, large bending, high low-temperature impact resistance, easy processing, and reusability.

[0051] Thermoplastic elastic nylon composite ultra-light elastomer is formed by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into polyamide elastomer, modifying the molecular chain in polyamide elastomer so that the soft segment molecular chain and the hard segment molecular chain of polyamide elastomer are mutually fused and completely fused with each component. Thermoplastic elastic nylon composite ultra-light elastomer has low melting point, light specific gravity, large foaming ratio, can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as the base material of soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0052] Polyborosiloxane is formed by the reaction of polydimethylsiloxane and boric acid at 250℃-300℃. In polyborosiloxane, the electron-deficient boron atom obtains electrons from the electron-carrying oxygen atom in the adjacent molecule, thereby forming a BO cross-linking bond. The BO cross-linking bond will absorb heat energy and activate and break at room temperature, so when subjected to force, the composite foam material will have the same deformation characteristics as plasticine. When encountering high-speed impact, because the action time is shorter than the thermal break time of the cross-linking bond, it can form a network structure of molecules, showing characteristics such as shock absorption and high rebound.

[0053] Ethylene-vinylacetate copolymer (EVA) has a vinyl acetate content of 5% to 40%. Compared with polyethylene, EVA has a low crystallinity and high flexibility, impact resistance, filler compatibility and heat sealing performance due to the introduction of vinyl acetate monomer into the molecular chain. It is widely used in the fields of foamed shoe materials, functional shed films, packaging films, hot melt adhesives, wires and cables, and toys. In the field of foamed shoe materials, the vinyl acetate content is generally 15% to 22%. Since EVA resin blended foam products have the properties of softness, good elasticity, and chemical corrosion resistance, they are widely used in the soles and interior materials of mid-to-high-end tourist shoes, mountaineering shoes, slippers, and sandals.

[0054] Foaming agents are substances that make the target substance pore-forming. They can be divided into three categories: chemical foaming agents, physical foaming agents, and surfactants. Chemical foaming agents are compounds that can release gases such as carbon dioxide and nitrogen after heating and decomposition, and form pores in the polymer composition; physical foaming agents are compounds whose foam pores are formed by the change of the physical form of a certain substance, that is, by the expansion of compressed gas, the volatilization of liquid, or the dissolution of solid. Foaming agents have high surface activity, can effectively reduce the surface tension of liquids, and arrange double electron layers on the surface of the liquid film to surround the air to form bubbles, and then single bubbles form foam.

[0055] In some embodiments, optionally, the foaming agent is one or a combination of two or more of azodicarbonamide, expandable sphere polymer, and OBSH foaming agent.

[0056] Surfactants are substances that can increase the activity of organic accelerators, allowing them to fully exert their effectiveness, thereby reducing the amount of accelerators used or shortening the vulcanization time.

[0057] In some embodiments, the activator is optionally one or a combination of stearic acid and zinc stearate. Stearic acid plays an important role in the synthesis and processing of rubber: stearic acid is a widely used vulcanization activator in natural, synthetic rubber and latex, and can also be used as a plasticizer and softener. Stearic acid can be added as an emulsifier in the production of synthetic rubber, stearic acid can be used as a foaming agent when making foam rubber, and stearic acid can also be used as a release agent for rubber products.

[0058] Bridging agent, the scientific name of bridging agent is blocked water-based curing agent (non-ionic cross-linking agent), and its aliases are bridging agent, curing agent, cross-linking agent, color fixative, adhesive, enhancer, reinforcing agent, and fastness enhancer. Its main component is blocked polyisocyanate. This series of curing agents can coexist stably with water-based resins (water-based polyurethane, water-based acrylate, fluorine emulsion, silicone emulsion, etc.) for a long time at room temperature. During heat treatment, the isocyanate (-NCO) group released by the curing agent reacts with the hydroxyl, carboxyl, amino and other groups on the water-based resin molecular chain to form a cross-linking structure, which can significantly improve the performance of the water-based resin.

[0059] In some embodiments, optionally, the bridging agent is dicumyl peroxide (DCP).

[0060] Coupling agent is a kind of substance with two functional groups of different properties. The biggest feature of its molecular structure is that it contains two groups with different chemical properties. One is an inorganic-friendly group that is easy to react chemically with the surface of inorganic substances; the other is an organic-friendly group that can react chemically with synthetic resins or other polymers or generate hydrogen bonds and dissolve in them. Therefore, coupling agent is called "molecular bridge" to improve the interface between inorganic and organic substances, thereby greatly improving the performance of composite materials, such as physical properties, electrical properties, thermal properties, optical properties, etc. Coupling agent is used in the field of soles to improve the wear resistance and aging resistance of soles, and can reduce the amount of NR, thereby reducing costs. The role of coupling agent in composite materials is that it can react with certain groups on the surface of reinforcing materials and react with matrix resins to form an interface layer between reinforcing materials and resin matrix. The interface layer can transmit stress, thereby enhancing the bonding strength between reinforcing materials and resins, improving the performance of composite materials, and at the same time preventing other media from penetrating into the interface, improving the interface state, and being beneficial to the aging resistance, stress resistance and electrical insulation properties of the products.

[0061] The present application adds polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer and polyborosiloxane to ethylene-vinyl acetate copolymer. Under the synergistic effect of the proportions of various components, the compression deformation and weight of the composite foam material are greatly reduced, so that the resilience of the composite foam material is greatly improved. The composite foam material is soft and comfortable, has excellent cushioning and resilience properties, and is excellent in wear resistance (far exceeding ordinary EVA foam materials), thereby meeting the performance requirements of sports shoe soles and providing consumers with a lasting comfortable experience.

[0062] In some embodiments, optionally, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, ethylene vinyl acetate copolymer;

[0063] Based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer,

[0064] The mass content of the polyamide elastomer is 35%-45%, the mass content of the thermoplastic polyurethane elastomer is 5%-10%, the mass content of the EPDM rubber is 5%-10%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 10%-15%, and the mass content of the ethylene vinyl acetate copolymer is 20%-45%.

[0065] Polyamide elastomer is a block copolymer containing aliphatic polyester or polyether soft segments and polyamide hard segments in the main chain of the molecule. Polyamide elastomers are divided into two categories, the hard segment is semi-aromatic amide, and the soft segment is aliphatic polyester, aliphatic polyether or aliphatic polycarbonate. The influence of the hard segment parameters is usually related to the crystallinity of the polyamide hard segment and the melting point of the hard micro-region crystallization. When the molecular weight of the hard segment is low, the crystallinity is large, the higher the melting point, and the higher the upper limit of the use temperature. In this way, the higher the phase separation, the softer the elastomer. The proportion of soft segments in the elastomer is relatively high. Its chemical composition has a great influence on the thermal oxidation stability. Polyether is more susceptible to oxidation forging than polyester, and polyester is less resistant to hydrolysis than polyether.

[0066] Thermoplastic polyurethane elastomer is made of high melting point crystalline Hard Segment ( Polyamide ) and amorphous Soft segment ( Polyester or Gather ether ), wherein the hard segment is PA-6, PA-66, PA-12, etc., and the soft segment is composed of polyether or polyester. Lactam , Dicarboxylic Acids , Gather Ether polyols The properties of the elastomer depend on the hard segment type and the two Block Due to the presence of hard segment polyamide, polyamide thermoplastic elastomer has excellent toughness , Chemical resistance , Wear-resistant sex By selecting and controlling the block type, its Mechanics , heat and Chemical Performance can vary over a wide range.

[0067] EPDM is a terpolymer of ethylene, propylene and non-conjugated diene. Among them, the diene has a special structure, only one of the two bonds can be copolymerized, and the unsaturated double bond is mainly used as a crosslink; the other unsaturated will not become the main chain of the polymer, but only a side chain. The main polymer chain of EPDM is completely saturated, making EPDMIt is resistant to heat, light, oxygen and especially ozone. EPDM is essentially non-polar, resistant to polar solutions and chemicals, has low water absorption and good insulating properties. During the EPDM production process, its properties can be adjusted by changing the amount of the three monomers, the ethylene-propylene ratio, the molecular weight and its distribution, and the method of vulcanization.

[0068] Hydrogenated styrene-butadiene-styrene block copolymer (English full name Styrene Ethylene Butylene Styrene, referred to as SEBS), SEBS does not contain unsaturated double bonds, it has excellent aging resistance, has both plasticity and high elasticity, can be processed and used without vulcanization, and the scraps can be reused. It is widely used in the production of high-end Elastomer , Plastic modification , adhesives, lubricant thickeners, fillers and sheathing materials for wires and cables, etc. SEBS has good weather resistance, heat resistance, compression deformation resistance and excellent mechanical properties. Specifically: (1) Good temperature resistance, its brittle temperature ≤-60°C, the maximum operating temperature reaches 149°C, and its decomposition temperature is greater than 270°C in an oxygen atmosphere. (2) Excellent aging resistance. After aging in an artificial accelerated aging box for one week, its performance decline rate is less than 10%, and after ozone aging (38°C) for 100 hours, its performance decline is less than 10%. (3) Excellent electrical properties, its dielectric constant is 1.3*10-4 at 1 kHz and 2.3*10-4 at 1 MHz; the volume resistivity is 9*1016Ω / cm for one minute; 2*1017Ω / cm for two minutes. (4) Good solubility, blending properties and excellent oil filling properties. It can be dissolved in many commonly used solvents. Solubility Parameters Between 7.2 and 9.6, it can be blended with a variety of polymers and can be extended with oils commonly used in the rubber industry, such as white oil or naphthenic oil. (5) It is an elastomer that can be used without vulcanization. Its processing performance is similar to that of SBS. The scraps can be reused. It meets environmental requirements, is non-toxic, and meets FDA requirements. (6) It has a light specific gravity of about 0.91, and the same weight can produce more volume products.

[0069] Ethylene-vinylacetate copolymer (EVA) has a vinyl acetate content of 5% to 40%. Compared with polyethylene, EVA has a low crystallinity and high flexibility, impact resistance, filler compatibility and heat sealing performance due to the introduction of vinyl acetate monomer into the molecular chain. It is widely used in the fields of foamed shoe materials, functional shed films, packaging films, hot melt adhesives, wires and cables, and toys. In the field of foamed shoe materials, the vinyl acetate content is generally 15% to 22%. Since EVA resin blended foam products have the properties of softness, good elasticity, and chemical corrosion resistance, they are widely used in the soles and interior materials of mid-to-high-end tourist shoes, mountaineering shoes, slippers, and sandals.

[0070] The present application modifies the molecular chains in the polyamide elastomer by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point and can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0071] In some embodiments, optionally, the polyborosiloxane is prepared by reacting polydimethylsiloxane with boric acid at 250° C.-300° C.

[0072] Polydimethylsiloxane is the chemical state of dimethyl silicone oil. Depending on the relative molecular mass, the appearance ranges from colorless and transparent volatile liquid to extremely high viscosity liquid or silica gel. It is odorless, highly transparent, heat-resistant, cold-resistant, with little viscosity change with temperature, waterproof, low surface tension, and thermal conductivity. The thermal conductivity coefficient is 0.134-0.159W / (m·K), and the light transmittance is 100%. Polydimethylsiloxane is non-toxic and odorless, physiologically inert, and has good chemical stability. It has good electrical insulation, weather resistance, and hydrophobicity, and has high shear resistance. It can be used for a long time at -50℃~200℃. It has excellent physical properties and can be directly used in moisture-proof insulation, damping, shock absorption, defoaming, lubrication, polishing, etc. It is widely used as insulation lubrication, shockproof, oil and dustproof, dielectric fluid and heat carrier. It can also be used as defoaming, release agent, paint and daily chemical additives.

[0073] Boric acid is an inorganic compound with the chemical formula H3BO3. It is a white crystalline powder with a slippery feel and no odor.

[0074] Polyborosiloxane is formed when electron-deficient boron atoms gain electrons from oxygen atoms with electron pairs in adjacent molecules, thereby forming BO cross-linked bonds. BO cross-linked bonds will absorb heat energy and activate and break at room temperature, so when subjected to force, the composite foam material will have deformation characteristics like plasticine. When encountering high-speed impact, because the action time is shorter than the thermal break time of the cross-linked bonds, it can allow the molecules to form a network structure, exhibiting characteristics such as shock absorption and high rebound.

[0075] Optionally, the reaction temperature of polydimethylsiloxane and boric acid is 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, or a value within the range obtained by combining any two of the above values.

[0076] In some embodiments, optionally, the mass ratio of the polydimethylsiloxane to the boric acid is 25:2-4. The present application can ensure that the electron-deficient boron atoms obtain sufficient electrons from the oxygen atoms with electron pairs in the adjacent molecules by reasonably controlling the mass ratio of the polydimethylsiloxane to the boric acid, thereby forming enough BO cross-linking bonds, so that the composite foam material can have the characteristics of compression deformation when subjected to force, and can form a sufficient network structure between the molecules when subjected to high-speed impact to show characteristics such as shock absorption and high resilience.

[0077] Optionally, the mass ratio of the polydimethylsiloxane to the boric acid is 25:2, 25:2.1, 25:2.2, 25:2.3, 25:2.4, 25:2.5, 25:2.6, 25:2.7, 25:2.8, 25:2.9, 25:3.0, 25:3.1, 25:3.2, 25:3.3, 25:3.4, 25:3.5, 25:3.6, 25:3.7, 25:3.8, 25:3.9, 25:4, or its value is within the range obtained by combining any two of the above values.

[0078] In some embodiments, the reaction time is optionally 70h-74h. The present application reasonably controls the reaction time of polydimethylsiloxane and boric acid to ensure that the electron-deficient boron atoms obtain sufficient electrons from the oxygen atoms with electron pairs in the adjacent molecules, thereby forming enough BO cross-linking bonds, so that the polyborosiloxane can play a greater role.

[0079] Optionally, the reaction time of the polydimethylsiloxane and the boric acid is 70 h, 70.5 h, 71 h, 71.5 h, 72 h, 72.5 h, 73 h, 73.5 h, 74 h, or a value within the range obtained by combining any two of the above values.

[0080] Reference Figure 1 , Figure 1 This is a flow chart for preparing ultra-light elastic composite foam materials according to some embodiments of the present application.

[0081] In a second aspect, the present application provides a method for preparing an ultra-light elastic composite foam material, the preparation method comprising the following steps:

[0082] Mixing once, placing the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent at 120° C.-150° C. for 7 min-10 min to form a first mixed material;

[0083] Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130°C-140°C for 2min-3min to form a second mixed material;

[0084] Granulation: placing the second mixed material at 80° C.-90° C. for granulation to form a composite material;

[0085] Foaming: placing the composite material at 160° C.-170° C. for foaming to form an ultra-light elastic composite foam material.

[0086] The present invention firstly blends polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene vinyl acetate copolymer, active agent, and bridging agent and performs a first banburying, then continues to add foaming agent and coupling agent for blending and a second banburying, then performs granulation and foaming, and finally obtains an ultra-light elastic composite foam material. The composite foam material is soft and comfortable, has excellent cushioning and rebound performance, excellent wear resistance (far superior to ordinary EVA foam material), and good recovery performance, thereby meeting the performance requirements of sports shoe soles and can bring consumers a lasting comfortable experience.

[0087] In some embodiments, optionally, the preparation method further comprises a step of preparing a thermoplastic elastic nylon composite ultra-light elastomer, and the preparation step is:

[0088] Adding polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer into a twin-screw extruder, blending and extruding, to obtain a thermoplastic elastic nylon composite ultra-light elastomer;

[0089] The blending time is 3 min-5 min, and the blending temperature is 200°C-230°C.

[0090] The present application modifies the molecular chains in the polyamide elastomer by adding thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into the polyamide elastomer, so that the soft segment molecular chains and the hard segment molecular chains of the polyamide elastomer are mutually fused, and are completely fused with the thermoplastic polyurethane elastomer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer to form a thermoplastic elastic nylon composite ultra-light elastomer. The thermoplastic elastic nylon composite ultra-light elastomer has a low melting point and can be blended and foamed with ethylene vinyl acetate copolymer, and can be used as a base material for soles, making the soles elastic, soft, and highly resistant to cracking due to external pressure.

[0091] Optionally, the blending time is 3 min, 3.1 min, 3.2 min, 3.3 min, 3.4 min, 3.5 min, 3.6 min, 3.7 min, 3.8 min, 3.9 min, 4.0 min, 4.1 min, 4.2 min, 4.3 min, 4.4 min, 4.5 min, 4.6 min, 4.7 min, 4.8 min, 4.9 min, 5 min, or its value is within the range obtained by combining any two of the above values.

[0092] Optionally, the blending temperature is 200°C, 202°C, 204°C, 206°C, 208°C, 210°C, 212°C, 214°C, 216°C, 218°C, 220°C, 222°C, 224°C, 226°C, 228°C, 230°C, or a value within the range obtained by combining any two of the above values.

[0093] On the third aspect, the present application provides a sole, which is made of an ultra-light elastic composite foam material that is foamed through a foaming mold and then heated, shaped, and cooled through a molding mold.

[0094] The present application utilizes ultra-light elastic composite foaming material to form an ultra-light elastic sole through foaming, heating, shaping and cooling, thereby reducing the weight of a single sole by about 60%. At the same time, the density of a single sole is only about 40% of the density of a traditional sole. In addition, the sole is soft and comfortable, has excellent cushioning and rebound properties, is excellent in wear resistance (far exceeding ordinary EVA foam soles), and has good recovery performance, which effectively solves the technical problem of the sole "becoming hard from soft and undergoing large permanent deformation" after long-term wear, greatly prolongs the service life of the sole, enhances the durability of the sole, and improves the wearer's wearing experience.

[0095] In some embodiments, optionally, the foaming temperature is 160° C.-180° C., and the foaming time is 400s-600s. The present application greatly improves the foaming ratio by reasonably controlling the foaming temperature and foaming time of the ultra-light elastic composite foaming material in the foaming mold.

[0096] Optionally, the foaming temperature is 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 178°C, 179°C, 180°C, or its value is within the range obtained by combining any two of the above values.

[0097] Optionally, the foaming time is 400s, 410s, 420s, 430s, 440s, 450s, 460s, 470s, 480s, 490s, 500s, 510s, 520s, 530s, 540s, 550s, 560s, 570s, 580s, 590s, or 600s, or its value is within the range obtained by combining any two of the above values.

[0098] In some embodiments, optionally, the heating temperature is 165°C-185°C, the heating time is 500s-700s, and the shaping pressure is 80kg / m 2 -100 kg / m 2 The present application improves the structural stability of the sole by reasonably controlling parameters such as heating and shaping.

[0099] Optionally, the heating temperature is 165°C, 166°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, or its value is within the range obtained by combining any two of the above values.

[0100] Optionally, the heating time is 500s, 510s, 520s, 530s, 540s, 550s, 560s, 570s, 580s, 590s, 600s, 610s, 620s, 630s, 640s, 650s, 670s, 680s, 690s, or 700s, or its value is within the range obtained by combining any two of the above values.

[0101] Optionally, the molding pressure is 80kg / m 2 , 81kg / m 2 、82kg / m 2 、83kg / m 2、84kg / m 2 、85kg / m 2 、86kg / m 2 、87kg / m 2 、88kg / m 2 、89kg / m 2 , 90kg / m 2 , 91kg / m 2 , 92kg / m 2 , 93kg / m 2 , 94kg / m 2 , 95kg / m 2 , 96kg / m 2 , 97kg / m 2 、98kg / m 2 , 99kg / m 2 , 100kg / m 2 , or its value is within the range obtained by combining any two of the above values.

[0102] Example 1

[0103] The present embodiment provides an ultra-light elastic composite foaming material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 10%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 35%, the mass content of the polyborosiloxane is 5%, the mass content of the ethylene-vinyl acetate copolymer is 45%, the mass content of the foaming agent is 1.0%, the mass content of the active agent is 2.4%, the mass content of the bridging agent is 0.4%, and the mass content of the coupling agent is 1.2%.

[0104] Among them, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer; based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer, the mass content of the polyamide elastomer is 35%, the mass content of the thermoplastic polyurethane elastomer is 5%, the mass content of the ethylene propylene diene monomer rubber is 5%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 10%, and the mass content of the ethylene vinyl acetate copolymer is 45%.

[0105] Reference Figure 2 , Figure 2 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 1 of the present application.

[0106] This embodiment provides a method for preparing an ultra-light elastic composite foam material, the preparation method comprising the following steps:

[0107] Pretreatment: adding polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer into a twin-screw extruder, blending (blending time is 3 minutes, blending temperature is 230° C.) and extruding to obtain a thermoplastic elastic nylon composite ultra-light elastomer;

[0108] Mixing once, kneading the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent at 120° C. for 10 minutes to form a first mixed material;

[0109] Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130° C. for 3 minutes to form a second mixed material;

[0110] Granulation, placing the second mixed material at 80° C. for granulation to form a composite material;

[0111] Foaming: placing the composite material at 160° C. for foaming to form an ultra-light elastic composite foam material.

[0112] This embodiment provides another sole, which is made of ultra-light elastic composite foam material through a foaming mold for foaming (foaming temperature is 160°C, foaming time is 600s), and then through a molding mold for heating (heating temperature is 165°C, heating time is 700s), shaping (shaping pressure is 80kg / m 2 ), and cooled.

[0113] Example 2

[0114] The present embodiment provides an ultra-light elastic composite foaming material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 12.5%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 40%, the mass content of the polyborosiloxane is 7.5%, the mass content of the ethylene-vinyl acetate copolymer is 32.5%, the mass content of the foaming agent is 2.25%, the mass content of the active agent is 3.2%, the mass content of the bridging agent is 0.55%, and the mass content of the coupling agent is 1.5%.

[0115] Among them, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer; based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer, the mass content of the polyamide elastomer is 40%, the mass content of the thermoplastic polyurethane elastomer is 7.5%, the mass content of the ethylene propylene diene monomer rubber is 7.5%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 12.5%, and the mass content of the ethylene vinyl acetate copolymer is 32.5%.

[0116] Reference Figure 3 , Figure 3 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 2 of the present application.

[0117] This embodiment provides a method for preparing an ultra-light elastic composite foam material, the preparation method comprising the following steps:

[0118] Pretreatment: adding polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer into a twin-screw extruder, blending (blending time is 4 minutes, blending temperature is 215° C.) and extruding to obtain a thermoplastic elastic nylon composite ultra-light elastomer;

[0119] In a first mixing process, the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent are mixed at 135° C. for 8.5 minutes to form a first mixed material;

[0120] Secondary mixing: adding the foaming agent and the coupling agent to the first mixed material, and mixing at 135° C. for 2.5 minutes to form a second mixed material;

[0121] Granulation, placing the second mixed material at 85° C. for granulation to form a composite material;

[0122] Foaming: placing the composite material at 165° C. for foaming to form an ultra-light elastic composite foam material.

[0123] This embodiment provides another sole, which is made of ultra-light elastic composite foam material through a foaming mold for foaming (foaming temperature is 170°C, foaming time is 500s), and then through a molding mold for heating (heating temperature is 175°C, heating time is 600s), shaping (shaping pressure is 90kg / m 2 ), and cooled.

[0124] Example 3

[0125] The present embodiment provides an ultra-light elastic composite foaming material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 15%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 45%, the mass content of the polyborosiloxane is 10%, the mass content of the ethylene-vinyl acetate copolymer is 20%, the mass content of the foaming agent is 3.5%, the mass content of the active agent is 4.0%, the mass content of the bridging agent is 0.7%, and the mass content of the coupling agent is 1.8%.

[0126] Among them, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer; based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer, the mass content of the polyamide elastomer is 45%, the mass content of the thermoplastic polyurethane elastomer is 10%, the mass content of the ethylene propylene diene monomer rubber is 10%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 15%, and the mass content of the ethylene vinyl acetate copolymer is 20%.

[0127] Reference Figure 4 , Figure 4 This is a flow chart for preparing the ultra-light elastic composite foam material of Example 3 of the present application.

[0128] This embodiment provides a method for preparing an ultra-light elastic composite foam material, the preparation method comprising the following steps:

[0129] Pretreatment: adding polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer into a twin-screw extruder, blending (blending time is 5 minutes, blending temperature is 200° C.) and extruding to obtain a thermoplastic elastic nylon composite ultra-light elastomer;

[0130] In a first mixing process, the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent are mixed at 150° C. for 7 minutes to form a first mixed material;

[0131] Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 140° C. for 2 minutes to form a second mixed material;

[0132] Granulation, placing the second mixed material at 90° C. for granulation to form a composite material;

[0133] Foaming: placing the composite material at 170° C. for foaming to form an ultra-light elastic composite foam material.

[0134] This embodiment provides another sole, which is made of ultra-light elastic composite foam material through a foaming mold for foaming (foaming temperature is 180°C, foaming time is 400s), and then through a molding mold for heating (heating temperature is 185°C, heating time is 500s), shaping (shaping pressure is 100kg / m 2 ), and cooled.

[0135] Comparative Example 1

[0136] The difference between the comparative example and the embodiment 1 is that the composite foam material in the comparative example 1 does not contain polyborosiloxane.

[0137] This comparative example provides a composite foaming material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, an ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 10%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 35%, the mass content of the ethylene-vinyl acetate copolymer is 50%, the mass content of the foaming agent is 1.0%, the mass content of the active agent is 2.4%, the mass content of the bridging agent is 0.4%, and the mass content of the coupling agent is 1.2%.

[0138] Among them, the thermoplastic elastic nylon composite ultra-light elastomer includes polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer; based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer, the mass content of the polyamide elastomer is 35%, the mass content of the thermoplastic polyurethane elastomer is 5%, the mass content of the ethylene propylene diene monomer rubber is 5%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 10%, and the mass content of the ethylene vinyl acetate copolymer is 45%.

[0139] Comparative Example 2

[0140] The difference between Comparative Example 2 and Example 1 is that the composite foam material in Comparative Example 2 does not contain any thermoplastic elastic nylon composite ultra-light elastomer.

[0141] This comparative example provides a composite foaming material, which includes a polyolefin elastomer, a polyborosiloxane, an ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 10%, the mass content of the polyborosiloxane is 5%, the mass content of the ethylene-vinyl acetate copolymer is 80%, the mass content of the foaming agent is 1.0%, the mass content of the active agent is 2.4%, the mass content of the bridging agent is 0.4%, and the mass content of the coupling agent is 1.2%.

[0142] Comparative Example 3

[0143] The difference between Comparative Example 3 and Example 1 is that: No thermoplastic elastic nylon composite ultra-light elastomer or polyborosiloxane is added in Comparative Example 3.

[0144] This comparative example provides a composite foaming material, which includes a polyolefin elastomer, an ethylene-vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 10%, the mass content of the ethylene-vinyl acetate copolymer is 85%, the mass content of the foaming agent is 1.0%, the mass content of the active agent is 2.4%, the mass content of the bridging agent is 0.4%, and the mass content of the coupling agent is 1.2%.

[0145] Comparative Example 4

[0146] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no pretreatment is performed on the polyamide elastomer.

[0147] This comparative example provides a composite foaming material, which includes a polyolefin elastomer, a thermoplastic elastic nylon composite ultra-light elastomer, a polyborosiloxane, a polyamide elastomer, a thermoplastic polyurethane elastomer, an ethylene propylene diene monomer rubber, a hydrogenated styrene-butadiene-styrene block copolymer, an ethylene vinyl acetate copolymer, a foaming agent, an active agent, a bridging agent, and a coupling agent; based on the total mass of the composite foaming material, the mass content of the polyolefin elastomer is 10%, the mass content of the polyborosiloxane is 5%, the polyamide elastomer is 25%, the thermoplastic polyurethane elastomer is 2%, the ethylene propylene diene monomer rubber is 2%, the hydrogenated styrene-butadiene-styrene block copolymer is 6%, the mass content of the ethylene vinyl acetate copolymer is 45%, the mass content of the foaming agent is 1.0%, the mass content of the active agent is 2.4%, the mass content of the bridging agent is 0.4%, and the mass content of the coupling agent is 1.2%.

[0148] This comparative example provides a method for preparing a composite foam material, which comprises the following steps:

[0149] Mixing once, placing polyolefin elastomer, polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene rubber, hydrogenated styrene-butadiene-styrene block copolymer, polyborosiloxane, ethylene vinyl acetate copolymer, active agent, and bridging agent at 120° C. for 10 minutes to form a first mixed material;

[0150] Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130° C. for 3 minutes to form a second mixed material;

[0151] Granulation, placing the second mixed material at 80° C. for granulation to form a composite material;

[0152] Foaming: placing the composite material at 160° C. for foaming to form an ultra-light elastic composite foam material.

[0153] Table 1 Physical property test results of composite foam materials obtained from Examples 1-3 and Comparative Examples 1-3

[0154]

[0155] Table 2 Physical property test results of the soles obtained in Examples 1-3 and Comparative Examples 1-4

[0156]

[0157]

[0158] It can be seen from Table 1-2 that various properties (hardness, density, resilience, tensile strength, thermal shrinkage, compressibility, elongation at break and delamination tear) of Examples 1-3 are better than those of Comparative Examples 1-3. The soles of Examples 1-3 are soft and comfortable, with excellent cushioning and resilience properties, excellent wear resistance (far exceeding ordinary EVA foam soles), and good recovery performance, which effectively solves the technical problem of "the sole becoming hard from soft and undergoing large permanent deformation" after long-term wear, greatly prolongs the service life of the sole, enhances the durability of the sole, and improves the wearing experience of the wearer.

[0159] In addition, due to the low mixing temperature in Comparative Example 4, the nylon particles cannot melt and disperse, and remain in the original particles. Therefore, the foamed material produced in Comparative Example 4 is of poor quality and cannot be made into soles, that is, physical property tests cannot be performed.

[0160] It should be understood that the embodiments disclosed in this application are not limited to the specific processing steps or materials disclosed herein, but should be extended to equivalent substitutions of such features understood by ordinary technicians in the relevant field. It should also be understood that the terms used herein are only used for the purpose of describing specific embodiments and are not meant to be limiting.

[0161] The "embodiment" mentioned in the specification means that the specific features or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present application. Therefore, phrases or "embodiment" appearing in various places throughout the specification do not necessarily refer to the same embodiment.

[0162] In addition, the described features or characteristics may be combined in one or more embodiments in any other suitable manner. In the above description, some specific details, such as thickness, quantity, etc., are provided to provide a comprehensive understanding of the embodiments of the present application. However, it will be understood by those skilled in the relevant art that the present application can be implemented without the above one or more specific details or can also be implemented using other methods, components, materials, etc.

Claims

1. An ultra-light elastic composite foam material, characterized in that: The composite foaming material comprises polyolefin elastomer, thermoplastic elastic nylon composite ultra-light elastomer, polyborosiloxane, ethylene vinyl acetate copolymer, foaming agent, active agent, bridging agent and coupling agent; Based on the total mass of the composite foam material, The mass content of the polyolefin elastomer is 10%-15%, the mass content of the thermoplastic elastic nylon composite ultra-light elastomer is 35%-45%, the mass content of the polyborosiloxane is 5%-10%, the mass content of the ethylene vinyl acetate copolymer is 20%-45%, the mass content of the foaming agent is 1.0%-3.5%, the mass content of the active agent is 2.4%-4.0%, the mass content of the bridging agent is 0.4%-0.7%, and the mass content of the coupling agent is 1.2%-1.8%; The thermoplastic elastic nylon composite ultra-light elastomer comprises polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer, and ethylene vinyl acetate copolymer; Based on the total mass of the thermoplastic elastic nylon composite ultra-light elastomer, The mass content of the polyamide elastomer is 35%-45%, the mass content of the thermoplastic polyurethane elastomer is 5%-10%, the mass content of the EPDM rubber is 5%-10%, the mass content of the hydrogenated styrene-butadiene-styrene block copolymer is 10%-15%, and the mass content of the ethylene vinyl acetate copolymer is 20%-45%; The preparation method of the composite foam material comprises the following steps: Mixing once, placing the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent at 120° C.-150° C. for 7 min-10 min to form a first mixed material; Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130°C-140°C for 2min-3min to form a second mixed material; Granulation: placing the second mixed material at 80° C.-90° C. for granulation to form a composite material; Foaming: placing the composite material at 160°C-170°C for foaming to form an ultra-light elastic composite foam material; The preparation method of the composite foam material also includes the preparation step of thermoplastic elastic nylon composite ultra-light elastomer, and the preparation step is: Add polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into a twin-screw extruder, blend and extrude to obtain a thermoplastic elastic nylon composite ultra-light elastomer, wherein the blending time is 3 min-5 min and the blending temperature is 200° C.-230° C.

2. The ultra-light elastic composite foam material according to claim 1, characterized in that: The polyborosiloxane is prepared by reacting polydimethylsiloxane with boric acid at 250°C-300°C.

3. The ultra-light elastic composite foam material according to claim 2, characterized in that: The mass ratio of the polydimethylsiloxane to the boric acid is 25:2-4.

4. The ultra-light elastic composite foam material according to claim 2, characterized in that: The reaction time for obtaining the polyborosiloxane is 70h-74h.

5. A method for preparing an ultra-light elastic composite foam material as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Mixing once, placing the polyolefin elastomer, the thermoplastic elastic nylon composite ultra-light elastomer, the polyborosiloxane, the ethylene vinyl acetate copolymer, the activator, and the bridging agent at 120° C.-150° C. for 7 min-10 min to form a first mixed material; Secondary mixing: adding the foaming agent and coupling agent to the first mixed material, and mixing at 130°C-140°C for 2min-3min to form a second mixed material; Granulation: placing the second mixed material at 80° C.-90° C. for granulation to form a composite material; Foaming: placing the composite material at 160°C-170°C for foaming to form an ultra-light elastic composite foam material; The preparation method also includes the steps of preparing a thermoplastic elastic nylon composite ultra-light elastomer, and the preparation steps are: Add polyamide elastomer, thermoplastic polyurethane elastomer, ethylene propylene diene monomer rubber, hydrogenated styrene-butadiene-styrene block copolymer and ethylene vinyl acetate copolymer into a twin-screw extruder, blend and extrude to obtain a thermoplastic elastic nylon composite ultra-light elastomer, wherein the blending time is 3 min-5 min and the blending temperature is 200° C.-230° C.

6. A shoe sole, characterized in that: The sole is made of the ultra-light elastic composite foam material according to any one of claims 1 to 4. The sole is made by foaming the ultra-light elastic composite foam material through a foaming mold, and then heating, shaping and cooling through a forming mold.

7. The sole according to claim 6, characterized in that The foaming temperature is 160°C-180°C, and the foaming time is 400s-600s.

8. The sole according to claim 6, characterized in that The heating temperature is 165℃-185℃, the heating time is 500s-700s, and the molding pressure is 80kg / m2-100 kg / m2.

Citation Information

Patent Citations

  • Environment-friendly foaming material forming method

    CN104552900A

  • Foaming material for shoes, preparation method and shoe

    CN111100369A

  • Light nylon elastomer foaming material and preparation method thereof

    CN111286102A

  • High-wear-resistance and high-shock-absorption sneaker sole material and preparation method thereof

    CN112625333A

Cited By

  • Low-viscosity polyborosiloxane and preparation method thereof

    CN116874793A

  • A low viscosity polyborosiloxane and a method for preparing the same

    CN116874793B